The Authentication Of Halal Dental Materials Using Rapid Fourier Transform Infrared (ftir) Spectroscopy - Azrul Hafiz Abdul Aziz; Mutalib, Nurul Asyikeen Ab; Rahman, Russly Abdul; Jaswir, Irwandi; Mirghani, Mohamed Elwathig Saeed; Octavianti, Fitri; Rahmadsyah, Adi (American Scientific Publishers, 2024)
Indexed by Scopus